SOCIOCULTURAL CONCEPTUALIZATION OF FEAR - Luknar, Ivana (Serbian political thought, 2023)
Fear is one of the basic human emotions that is due to the safety need and preservation of life. The phenomenon of fear is closely related to the social structure and significantly influences the behavior of actors. The paper shows the instrumentalization of fear as a mechanism of social control. Fear is a multidimensional phenomenon (biological, psychological, cultural and social dimensions of fear) and its interpretation requires the application of the multidisciplinary approach. In the paper is applied the method of content analysis of professional literature and sociological discourse, on which the terms of fear and its theoretical propositions were conceptualized. The paper aims to start a debate on the mentioned topic. Key words: fear, instrumentalization of fear, sociocultural determinants of fear